Reactogenicity and immunogenicity of the second COVID-19 vaccination in patients with inborn errors of immunity or mannan-binding lectin deficiency - Göschl, Lisa; Mrak, Daniel; Grabmeier-Pfistershammer, Katharina; Stiasny, Karin; Haslacher, Helmuth; Schneider, Lisa; Deimel, Thomas; Kartnig, Felix; Tobudic, Selma; Aletaha, Daniel; Burgmann, Heinz; Bonelli, Michael; et al. (Frontiers in Immunology, 2022)
Background Patients with inborn errors of immunity (IEI) are at increased risk for severe courses of SARS-CoV-2 infection. COVID-19 vaccination provides effective protection in healthy individuals. However, it remains unclear whether vaccination is efficient and safe in patients with constitutional dysfunctions of the immune system. Thus, we analyzed the humoral response, adverse reactions and assessed the disease activity of the underlying disease after COVID-19 vaccination in a cohort of patients suffering from IEIs or mannan-binding lectin deficiency (MBLdef). Methods Vaccination response was assessed after basic immunization using the Elecsys anti-SARS-CoV-2 S immunoassay and via Vero E6 cell based assay to detect neutralization capabilities. Phenotyping of lymphocytes was performed by flow cytometry. Patient charts were reviewed for disease activity, autoimmune phenomena as well as immunization status and reactogenicity of the vaccination. Activity of the underlying disease was assessed using a patient global numeric rating scale (NRS). Results Our cohort included 11 individuals with common variable immunodeficiency (CVID), one patient with warts hypogammaglobulinemia immunodeficiency myelokathexis (WHIM) syndrome, two patients with X-linked agammaglobulinemia (XLA), one patient with Muckle Wells syndrome, two patients with cryopyrin-associated periodic syndrome, one patient with Interferon-gamma (IFN-gamma) receptor defect, one patient with selective deficiency in pneumococcal antibody response combined with a low MBL level and seven patients with severe MBL deficiency. COVID-19 vaccination was generally well tolerated with little to no triggering of autoimmune phenomena. 20 out of 26 patients developed an adequate humoral vaccine response. 9 out of 11 patients developed a T cell response comparable to healthy control subjects. Tested immunoglobulin replacement therapy (IgRT) preparations contained Anti-SARS-CoV-2 S antibodies implicating additional protection through IgRT. Summary In summary the data support the efficacy and safety of a COVID-19 vaccination in patients with IEIs/MBLdef. We recommend evaluation of the humoral immune response and testing for virus neutralization after vaccination in this cohort.